Include, integrate, indivdiualize: A framework to guide effective managerial practice for an age diverse workforce - Petery, Gigi; Andrei, Daniela; Parker, Sharon (2019)
As the working population is both getting older and also more age diverse, current management paradigms are likely to be challenged. Despite this, few organizations are proactive in addressing this challenge, with current statistics showing that only about 8% of CEOs actually specifically mention age in their diversity strategies. In a similar fashion, scholars have recently drawn attention to the fact that existing research is not able to adequately support organizations and managers in effectively managing ageing and age diversity for better individual and organizational outcomes. For example the review conducted by Truxillo, Cadiz, and Hammer (2015) concluded that there is practically no research on interventions and best practices to support the ageing workforce, while Ali and French (2019)highlight that very little is known about which age diversity practices and interventions are effective, in which organizations and for which outcomes. The Centre for Excellence in Population Ageing (CEPAR) is aiming to address this challenge through its research stream focusing on Mature Workers and Organizations. The main focus of this research stream is to facilitate effective organizational interventions and practices to support not only successful ageing through work but also increased team and organizational productivity through an effective management of an age diverse workforce. As part of the CEPAR’s involvement with organizations participating in this research stream, we have developed a framework aimed at providing practical, evidence-based guidance to organizations looking to implement interventions or programs as part of their collaboration with CEPAR. The proposed framework focuses attention on three broad sets of approaches, or meta-strategies: Include, Individualize, and Integrate. Include brings forward strategies and interventions aimed at ensuring that employees of all ages feel fully welcome and valued at work through reduced bias and stereotypes. Individualize builds on life span development theories to focus on strategies and interventions aimed at enabling uniqueness through the adjustment of work and work structures to the changing needs and capabilities. Integrate builds on configural approaches to group composition and diversity to focus attention on actions and interventions aimed at ensuring that organizations reap the benefits of an age diverse workforce through effectively creating synergy out of diversity. The proposed poster will provide an overview of this framework, detailing its scientific underpinnings as well as implications for practice and intervention research conducted within the Mature Workers in Organizations research program.